PENGGUNAAN METODE ABA (APPLIED BEHAVIOR ANALYSIS) UNTUK MENINGKATKAN PEMAHAMAN ANAK AUTIS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SLB NEGERI PANDAAN - Ahmad Ma’ruf Lailatul Maghfiroh (Universitas Yudharta Pasuruan, 2017)
Children with autism are children who have very complex developmental disorders ranging from interference in language or communicate both verbal and non verbal, not easy to adjust or change the routine with around, doing a thing by repeating, until the interaction of social interaction. In essence, children with autism also need education as other normal children, because actually children with autism also have the potential that can be developed. These potentials can be maximized if appropriate treatment is received. Children with autism in addition to having general knowledge as well as other normal children, they also have to get a religious science in this case that is Islamic religious education in order to provision their spiritual. Because Islamic religious education will lead autistic children into people who are able to live their lives by directing them to have good morals in community life, as well as relationship with God. The key to the success of this learning process is determined by several components, including teachers, methods used, and so forth. A suitable method of handling autistic children is the ABA method.This study aims to analyze the use of ABA (Applied Behavior Analysis) Method to Improve Autism Children's Understanding on Islamic Education Learning in SLBN Pandaan, Pasuruan. The research approach used is qualitative descriptive approach. The focus of this research is the students of autism at elementary level in SLB Negeri Pandaan. Data collection techniques include: observation method, interview method and documentation method.Based on the results of research that has been done for 1 month through observation, interviews and documentation can be concluded that the use of ABA method (Applied Behavior Analysis) to students who experience autism in learning Islamic Religious Education gives influence to changes in behavior and responses of students in receiving learning Education Islam. Students are able to be more focused and responsive to instruction of Educator especially in learning of Islamic Education.